Al-Aṣwāt wa-Dalālātuhā ʿinda Ibn Taymīyah - Rizki Gumilar; Achmad Tito Rusady; Nur Imansyah (Alsina : Journal of Arabic Studies, 2025)
Phonetic problems in Arabic are classic problems studied since the age of Al-Khalil bin Ahmed Al-Farahidi (d. 170 AH). This science is still being studied and developed to this day and has even become something that cannot be separated from linguistics. Ibn Taymiyah was an expert in religious knowledge who paid great attention to sound and its meaning. On this basis, through the use of semantic descriptive analysis, this research seeks to collect opinions regarding the meaning of sounds and at the same time compare them with what ancient and contemporary phonetic scholars have put forward regarding this issue. Among the results obtained from this research is the correspondence between the sounds in Arabic and the meaningThe phonetic intensity of a sound corresponds to the semantic intensity of its meaning, and vice versa. This study is really needed by Arabic language students, because some of them have difficulty memorizing Arabic vocabulary which is so large and cannot be distinguished from one another except by just one letter or just one vowel. Not only that, it is hoped that this research can contribute to knowledge on the topic of discussing semantics and phonetics.